2014
DOI: 10.1161/strokeaha.114.006110
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Trait and Incident Ischemic Stroke in the Atherosclerosis Risk in Communities Study

Abstract: Background and Purpose Numerous case reports describe stroke in individuals with sickle cell trait (SCT) in the absence of traditional risk factors for cerebrovascular disease. To date, no prospective epidemiological studies have investigated this association. Methods A population-based sample of African Americans (N=3,497, mean age=54, female=62%) was followed from 1987–2011 in the Atherosclerosis Risk in Communities Study (ARIC), contributing a total of 65,371 person-years. Hazard ratios and incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
2
49
2
Order By: Relevance
“…It was observed that incident stroke is more frequents among SCT subjects compared to their homozygous HbA counterparts [27] tension and diabetes mellitus. The adjustment for these covariates might have reduced the effect of the observed association since hypertension is likely to be an intermediate factor in the progression to chronic kidney disease by SCT.…”
Section: Incident Strokementioning
confidence: 99%
“…It was observed that incident stroke is more frequents among SCT subjects compared to their homozygous HbA counterparts [27] tension and diabetes mellitus. The adjustment for these covariates might have reduced the effect of the observed association since hypertension is likely to be an intermediate factor in the progression to chronic kidney disease by SCT.…”
Section: Incident Strokementioning
confidence: 99%
“…The difference was not statistically significant. In multivariable analysis that controlled for the traditional risk factors for stroke, sickle cell trait was associated with a 40% higher risk of stroke [20]. Despite this, further investigation of the incidence and pathophysiology of stroke in patients with sickle cell trait is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there has not been any significant difference in the outcomes of stroke for sickle cell patients compared with normal haemoglobin [19]. In order to shed more light on this debatable association, a 24-year prospective epidemiological study was recently conducted observing an increased risk of ischaemic stroke in blacks with sickle cell trait [20]. In this study, the frequency of ischaemic stroke was slightly higher with sickle cell trait (13%) than in participants with normal adult haemoglobin (10%).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, suggest SCT may confer a higher risk for chronic kidney disease, thrombosis, stroke, and pregnancy-related complications in its carriers. [1][2][3][4][5][6] Importantly, there is growing concern SCT may be associated with sudden death during strenuous physical activity and exercise, leading to the National College Athletics Association to mandate carrier status testing among all student athletes in division I institutions in 2010, and later in all division II and III institutions. [7][8][9] Growing evidence suggests SCT carriers may exhibit abnormal physiologic responses to cardiopulmonary exercise testing when compared with controls without SCT.…”
Section: Introductionmentioning
confidence: 99%